PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP LOYALITAS PENGGUNA SRIWIJAYA AIR DI BANDARA INTERNASIONAL KUALANAMU MEDAN - Citra Yanti Pakpahan; I Wayan Suardana; I Made Kusuma Negara (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
The purpose of this study is to study the majority of service quality and brand image of the service user loyalty offered by Sriwijaya air. The determination of the sample in this study used a purposive sampling method of 250 respondents. Data collection techniques using questionnaires, and literature study. Data analysis techniques in this study were descriptive analysis, multiple linear regression analysis, validity and reliability, comparative analysis, hypothesis testing, and coefficient of determination analysis using SPSS version 18.0.The results of this study indicate the quality of service and brand image on the loyalty of service users who are supported by Sriwijaya Air at Kualanamu International Airport, Medan, which is stated to have a significant and partially significant effect simultaneously with a value of 72.2%. For service quality variables get the results of analysis with a t test of 7.140 and brand image of 3.809. The data of this study were obtained from distributing online questionnaires to respondents who had used Sriwijaya Air at Kualanamu International Airport, Medan.